Assessment of the effectiveness of replacing purified terephthalic acid (PTA) by QTA in textile production in Vietnam - Sang Nguyen Thanh; Mai Dang Thi Tuyet (Petrovietnam Journal, 2017)
Terephthalic acid (TA) is the main raw material for production of polyester in the world. There are two kinds of this acid: purified TA (PTA) and qualified TA (QTA). Basically, PTA and QTA production technologies are very similar in some stages and the quality of these two kinds of TA is not much different. However, due to the fact that QTA production technology is much simpler than PTA, QTA cost is cheaper. Therefore, using QTA to replace partially or completely PTA in polyester production will help reduce the raw material cost and increase the profit for the plant. The paper summarises the polyester production technology, QTA and PTA market information, and the difference in production technology between PTA and QTA. On that basis, the authors analyse TA influence on the synthesis of polyester in order to assess the possibility of using QTA to replace PTA for the fibre production plants in Vietnam.